2008
DOI: 10.1097/mej.0b013e3282efdd7a
|View full text |Cite
|
Sign up to set email alerts
|

To study the effectiveness and safety of ketamine and midazolam procedural sedation in the incision and drainage of abscesses in the adult emergency department

Abstract: The objective of the report was to study the efficacy and safety of ketamine and midazolam combination in the procedural sedation of incision and drainage of abscesses in the adult emergency department (ED) patients. This prospective observational study enrolled patients aged 16-60 years (American Society of Anesthesiologists class I) requiring abscess drainage in an adult ED. Patients received 2 mg/kg of ketamine infusion over 5 min and midazolam 2-5 mg titrated to deep sedation according to Ramsay sedation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…After screening the titles and abstracts and removing duplicates, we identified 465 potentially relevant studies. After full‐text review, 55 articles met inclusion criteria . Interobserver agreement (kappa) for phase II of the review was 0.99 (95% CI = 0.98 to 1.0).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening the titles and abstracts and removing duplicates, we identified 465 potentially relevant studies. After full‐text review, 55 articles met inclusion criteria . Interobserver agreement (kappa) for phase II of the review was 0.99 (95% CI = 0.98 to 1.0).…”
Section: Resultsmentioning
confidence: 99%
“…Ketamine and ketamine/propofol had the highest rate of agitation. Among the studies that used ketamine, the incidence of agitation was 164.1 per 1,000 sedations (95% CI = 94.8 to 233.5), and among those receiving ketamine/propofol, 48.1 per 1,000 sedations (95% CI = 12.9 to 83.3; see Figure ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 More recently adult studies have shown ketamine to produce effective sedation for procedures with benefits including less hemodynamic instability and improved pain control and the most commonly noted side effect being recovery agitation that can be mitigated with midazolam. [14][15][16][17] Ketamine also has been noted to have analgesic properties and to provide opioid-sparing effects. [18][19][20][21][22][23][24] Despite these properties, to our awareness it has never been reported in the literature for use in analgesia or sedation for terminal ventilator weaning.…”
Section: Discussionmentioning
confidence: 97%
“…We chose ketamine, as discussed below, as a rescue agent for agitation and as an analgesic adjunct based on its use for sedation in emergency medicine and in the anesthesia literature as well as its differing mechanism of action than the medications she was currently receiving. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Ketamine is an N-methyl-D aspartase (NMDA) receptor antagonist with known dissociative D. M. Noreika and P. Coyne 39 anesthetic properties. The analgesic and sedative effects that it produces are largely believed to be related to NMDA receptor blockade in the central nervous system and at the spinal cord level, although they additionally may be related to a complex interaction with opioid mu and kappa receptors.…”
Section: Discussionmentioning
confidence: 99%